Measuring patient and carer experience related to paediatric gastrointestinal endoscopy: multicentre questionnaire study. Issue 6 (13th January 2020) - Wan, Jessica Wai Yan; Griffiths, Elizabeth; Rabone, Rosalind; Zuhair, Zahmeena; Londt, Zuzana; Rawat, David; Maginnis, Janis; Elzubair, Amal; Pigott, Anna; Thomson, Mike; Narula, Priya
Abstract : Background: The Paediatric Endoscopy Global Rating Scale (P-GRS) is a quality improvement tool used in the UK. An important aspect of this includes regular surveys on the patient and/or carer's endoscopy experience. The aim of our study was to design and implement a patient/carer experience questionnaire. Methods: This questionnaire was designed to obtain feedback on patient and/or carer satisfaction with their endoscopy experience. Question selection was based on relevant measures in the endoscopy Global Rating Scale, with input from clinical governance, Patient Advice and Liaison Service and a hospital youth forum. This was distributed to patients and/or carers in three UK paediatric endoscopy services during six surveys between 2013 and 2018. Data were then collated and analysed on Microsoft Excel for Office 365 MSO (16.0.11901.20070). Results: Overall, 830 endoscopic procedures occurred during the six survey periods. 270 questionnaires were returned. Feedback from the questionnaires were mostly positive (overall satisfaction rated 'excellent' or 'good' was seen in 87% of responses) but also identified areas of improvement, such as in managing postprocedure pain and having a separate space for adolescents for preprocedure discussions. Improvements in satisfaction scores were noted in one unit over time, particularly in preprocedure preparation (from 86% to 100%), and overall satisfaction with endoscopy experience (81%–100%). Conclusion: All three paediatric endoscopy services found this questionnaire useful in identifying areas needing improvement and in demonstrating compliance with measures within the P-GRS quality of patient experience domain. Further work includes exploring ways to increase response rates, as well as developing age-appropriate and electronic versions.